Association Between Curve Magnitude in Scoliosis and Low Body Mass Index - Alya Roza Lisanti; Basuki Supartono; Feda Anisah Makkiyah; Prita Maya Savitri (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2025)
Background: Adolescent idiopathic scoliosis is a spinal deformity characterized by Cobb angle deviation of more than 10o. Objective: This study aims to determine the association between low body mass index (BMI) and curve magnitude in adolescent idiopathic scoliosis. Methods: This was a retrospective cohort study using medical record data of patients diagnosed with scoliosis at Bhayangkara Tk I Pusdokkes Polri Hospital. BMI classification was based on WHO BMI-for-ages z-scores in children and adolescents. Result: The study included 22 AIS subjects, with the majority aged 14–17 years and a higher proportion of females than males. The p-value for the association between low body mass index and adolescent idiopathic scoliosis is 0.169. Conclusion: Curve magnitude is not associated with low body mass index.